Updates in venous thromboembolism management: evidence published in 2016. Issue 3 (27th May 2017) - Bartlett, Matthew; Mauck, Karen F.; Bierle, Dennis M.; Saadiq, Rayya A.; Daniels, Paul R.
ABSTRACT: The management of venous thromboembolic disease (VTE) is rapidly evolving and staying updated on practice-changing evidence can be challenging. In an attempt to alleviate this daunting task, we sought to determine the most important practice-informing articles published in 2016 relevant to the non-specialist provider managing VTE. We performed a systematic search of the literature, limiting the search to a publication date of 2016 (see Supplementary Appendix). Two reviewers screened the 3819 resulting abstracts to identify high-quality, clinically relevant publications related to VTE management. Two hundred sixteen full-text articles were considered for inclusion. The five authors used a modified Delphi method to reach consensus on inclusion of 7 articles for in-depth appraisal, following predetermined criteria of clinical relevance to non-specialist providers, potential for practice change, and strength of the evidence.